Cannabis Use Disorder Treatment Preferences: A Pilot Survey in Current Users of Cannabis. Issue 2 (24th March 2023) - Lile, Joshua A.; Turner, Brian W.; Cox, David H.; Bonn-Miller, Marcel O.; Katz, Ned R.; Shellenberg, Thomas P.; Stoops, William W.; Strickland, Justin C.
Abstract : Objectives: Highly effective treatments for cannabis use disorder (CUD) are lacking, and patient preferences have not been considered during treatment development. We therefore conducted an exploratory crowdsourced survey of individuals reporting current cannabis use and a willingness to cut down or quit their cannabis use, to determine their interest in various treatment aspects. Methods: Subjects (n = 63) were queried about their willingness to take medications as a function of type, route, and regimen and to participate in adherence monitoring. Subjects were also asked about their willingness to engage in behavioral/psychosocial interventions as a function of type, setting, and duration. Measures theorized to be associated with treatment preferences were also collected, including cannabis use variables, readiness to change, reduction or cessation goal, perceived cessation barriers, and medication use beliefs and behaviors. Results: Survey responses indicated that efforts to develop CUD medications should focus on nonsynthetic compounds administered orally or by mouth spray no more than once per day to maximize patient acceptance. Remote adherence monitoring and one-on-one outpatient behavioral treatment approaches, especially contingency management, are also anticipated to enhance participation. Most subjects indicated a preference to reduce their cannabis use rather than quit. Conclusions: These data provide guidance for the development of CUD interventions based on the preferences of individuals interested in treatment for their cannabis use. Additional research is needed to confirm these results in a larger sample and determine if matching CUD patients with their preferred treatments improves success rates.